Brain Basics Module for MOOC and Brain awareness for secondary school in Sarawak, 2017-2018 - Norsiah, Fauzan; Ahmad Sofian, Shminan; Herman Sah, bin AB Hassan (2017)
The purpose of developing the module for MOOC and brain Awareness is to spread the knowledge of neuroscience to the learning community in Sarawak. The large populations of learning community (urban and rural) will be able to access the MOOC. The instructional material will be uploaded to MOOC to assist their understanding and create awareness among the secondary school children throughout sarawak.